Public Debt Markets in Central America, Panama, and the Dominican Republic - Jobst, Andreas (IMF Working Papers; Working Paper, 2007)
This paper-consisting of a regional study and seven country studies-reviews the state of domestic public debt markets in Costa Rica, Dominican Republic, El Salvador, Guatemala, Honduras, Nicaragua, and Panama as at end-2005. Although they account for the lion's share of capital markets, regional public debt markets remain underdeveloped for a variety of reasons. The problems of small scale, dollarization, and weak public finances in many countries are compounded by poor structure and composition of debt (with sizeable nonstandard and non-tradable components), fragmentation of public debt between central banks and the sovereigns and across instruments, poor debt management practices, weaknesses in securities market, and small investor bases all of which result in high transaction costs and a lack of liquid benchmarks. The paper also briefly discusses efforts towards and impediments to regional integration of public debt markets. The authorities recognize these problems and the paper takes note of the regional efforts to harmonize debt standards and improve issuance practices. It offers several recommendations to improve strategic debt management, issuance mechanics, and secondary trading.